PENGARUH KONSEP KAIZEN (5S) TERHADAP PENINGKATAN DAYA SAING USAHA KECIL DAN MENENGAH (UKM) - S, Netty Laura; Paramita, Catarina Cori Pradnya (Jurnal Pengabdian dan Kewirausahaan, 2018)
This study looks at the phenomenon of the sector of Small and Medium Enterprises (SMEs) have a very strategic and important role that can be reviewed from various aspects. It takes the right concept to improve SMEs by implementing the Kaizen Concept (5s) which is a concept already used by big companies. This research is conducted to know the effect of Kaizen Concept on Improving Competitiveness of SMEs. The study used primary data with the dissemination of research questionnaires. Respondents of this research are all SMEs in North Jakarta. The results of this study explain that Aspect Seiri (compact) (X1) has a significant influence on Competitiveness of SMEs (Y). Seiton (Rapi) (X2) has a significant effect on the competitiveness of SMEs in North Jakarta, Seiso Aspect (Resik) (X3) has a significant effect on SME Competitiveness (Y) in North Jakarta. Respondents perceive Seiso (Resik) that belongs quite high. Seiso contribution (Resik) to SME's Competitiveness is explained by 35.7%. Seiketsu aspect (Rawat) (X4) gives a significant influence to SME Competitiveness (Y) in North Jakarta. This means that the better Seiketsu (Rawat) (X4) it will be good also Competitiveness of SMEs (Y) in North Jakarta. The Shitsuke (Rajin) aspect is not significant in influencing the Competitiveness of SMEs in North Jakarta. Simultaneously, Seiri variables, Seiton (Rapi), Seiso (Resik), Seiketsu (Rawat), Shitsuke (Rajin), show a positive and significant impact on SME Competitiveness. Keywords: Kaizen (5s), Competitiveness, Small and Medium Enterprises (SMEs)